Some effects of ‘pre-crime’ concept in combating domestic violence - Marković, Saša M.; Kolarić, Dragana (NBP. Nauka, bezbednosti, policija, 2023)
Abstract: The paper discusses the role of police, public prosecutor and court in combating domestic violence and the effects achieved in the 2018-2021 period. The competent state bodies have at their disposal various measures that they can choose from in order to protect victims and combat violence. However, certain procedures are to be followed. Since the adoption of the Law on Prevention of Domestic Violence, the actions of police and judicial bodies have been based on the pre-crime concept, as the focus is on preventing the perpetration of the criminal offence. The measures are applied even where there has been no violence but the behaviour of the prospective perpetrator indicates that he may commit violence for the first time in the immediate future. Proactive work involves actions aimed at the source of potential problems, performing a risk assessment based on the analysis of available data and making decisions that will solve (neutralize) the observed problem and prevent domestic violence. If violence occurs, criminal law shall apply post delictum which, in addition to its most repressive character, also has a preventive dimension. Criminal law is ultima ratio and represents a significant and ultimate means aimed at protecting the victim. We started from a general hypothesis that existing legal regulations in Serbia offer adequate mechanisms for the police and judicial bodies to timely and efficiently oppose domestic violence. On the basis of such a general hypothesis we proposed the following individual hypotheses: 1) The effectiveness in protecting victims of domestic violence depends on the efficacy of police and effects of taken measures. 2) Risk assessment of domestic violence is performed by the police in an appropriate manner. 3) Timely implementation of provisions of the Law on Prevention of Domestic Violence results in a decreased number of criminal offences of domestic violence. 4) Cooperation of competent authorities and combination of preventive and repressive measures is a crucial aspect of combating domestic violence. The aim of the study is to establish whether the provisions of the law that empower the police and judicial bodies are adequately implemented in the entire territory of the Republic of Serbia and whether they offer sufficient mechanisms to efficiently and effectively prevent and suppress domestic violence and provide efficient protection of the victims. We will also establish what the sentencing policy of the courts is and how efficient the public prosecution is in suppressing domestic violence.
Keywords: domestic violence, risk assessment, emergency/urgent measures, criminal offence, sanction.